Influence of incorporating honey, royal jelly and pollen on biotechnological processes of dairy drink - Ломова, Неонила Николаевна; Снежко, Ольга Олеговна (Eastern-European Journal of Enterprise Technologies, 2014)
The influence of adding bee honey, royal jelly and pollen on the incubation time, smell, taste and texture of dairy drink, obtained by the fermentation of starter cultures such as Lac. Lactis, Str. Thermophilus, Lbm. Acidophilum, Lbm. Bulgaricum, kefir, combined (⅓ Str. Thermophilus, ⅓ Lbm. Acidophilum, ⅓ Lbm. Bulgaricum) was studied. The nature of influence of bee products on the yogurt microflora, including the third and sixth day of storage was studied. Increasing the viability of yogurt microorganisms was proportionalto the concentration of honey, pollen and royal jelly to a certain level. Further, the reverse process was observed. Based on the preliminary results, a starter culture with which bee products are combined in the best way was defined. A possible dose of honey, royal jelly and bee pollen for the production of yoghurt with bee products was selected.